India Development Update, October 2013 - World Bank (Washington, DC, 2014)
Although the recent market turmoil has been driven primarily by external factors, it has magnified India's macroeconomic vulnerabilities. India was just one of a large number of emerging market economies whose currency and capital account were adversely affected by a large outflow of portfolio investment this summer. The current downturn presents an opportunity to push ahead with critical reforms. The current situation is unlikely to place an insurmountable stress on the economy, but it does offer an opportunity for measures to strengthen the business environment, attract more Foreign Direct Investment (FDI), and increase productivity. The rupee depreciated sharply in May-August 2013, mainly caused by market fears of an early end to the Federal Reserve's stimulus program. As global investors shifted funds into US treasuries, the May-August fall in the rupee closely mirrored movements in other emerging market currencies and US T-bonds. The current account deficit moderated and exports performance improved. After reaching a record high of 6.5 percent of Gross Domestic Product (GDP) in the third quarter FY2013, the current account deficit improved to 3.6 percent of GDP in the fourth quarter. The decline in poverty has accelerated, but vulnerability remains high. Between 2005 and 2012, India lifted 137 million people out of poverty and reduced the poverty headcount (at the national poverty line) to 22 percent of the population. The depreciation in the rupee is unlikely to have major adverse effects and provides an opportunity to accelerate growth through further progress on the reform agenda. Financing of the gap is expected to come in roughly equal parts from FDI and institutional flows in FY2014, with a growing contribution from FDI in FY2015.